2022
DOI: 10.1126/sciimmunol.abn5859
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral immunotherapy relies on B and T cell collaboration

Abstract: Antitumor T cell responses are the primary mediators of cancer immunotherapy. However, many other components of the immune system are needed for efficient T cell responses to be generated. Here, we developed a combinatorial approach where a Toll-like receptor 9 agonist (CpG) and Fc-fused IL-12 protein were injected together into just one of several tumor sites in a mouse. This combination led to body-wide (abscopal) therapeutic responses in multiple cancer models. These systemic responses were dependent not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The role of B cells in promoting antitumoral immune responses is increasingly recognized, with recent studies showing that B cells can act as APCs to T cells. [44][45][46][47] Hence B cell responses could enhance T cell responses to mRNA-LNP vaccines by multiple mechanisms, ranging from cytokine production to direct roles in antigen presentation themselves. Of note, as B cells contribute to the generation and maintenance of functional CD4 and CD8 T cells 48,49 and help in the organization of lymphoid organ architecture, 50 it cannot be ruled out that mMT mice are intrinsically less competent in responding to mRNA-LNP immunization compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B cells in promoting antitumoral immune responses is increasingly recognized, with recent studies showing that B cells can act as APCs to T cells. [44][45][46][47] Hence B cell responses could enhance T cell responses to mRNA-LNP vaccines by multiple mechanisms, ranging from cytokine production to direct roles in antigen presentation themselves. Of note, as B cells contribute to the generation and maintenance of functional CD4 and CD8 T cells 48,49 and help in the organization of lymphoid organ architecture, 50 it cannot be ruled out that mMT mice are intrinsically less competent in responding to mRNA-LNP immunization compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…On this note, a recent paper highlighted that antitumor efficacy of intratumoral immunotherapy is dependent on both T and B cells. [ 41 ] Negatively regulated lymphocytes, detected using Foxp3+ or CD8+PD‐1+, showed decrease density in the CD40 mAb treated groups (Figure 4C,D). Moreover, the treated tumors showed decrease of cancer cells (PanCK+) and angiogenesis ( α SMA+) in the TIME (Figure 4E,F).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study has reported that B-and T-cell collaboration is crucial for the efficacy of intratumoral immunotherapy. 36 For the development of cancer vaccines, several boost injections are generally required after the initial vaccination. However, a single injection of OVA@PS3 was enough to elicit potent immune responses against a cancer antigen as a prophylactic vaccine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%